ANALISIS STRATEGI PROYEK REPARASI KAPAL DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Ira Yulia Utami; Fitri Hardiyanti; Yugowati Praharsi (Proceeding Maritime Business Management Conference, 2024)
The performance of ship repair projects at a shipyard company in East Java has not reached optimal levels, as evidenced by the inability to meet project completion targets. This study aims to analyze internal and external factors, formulate performance improvement strategies, and prioritize these strategies. The analysis identified 6 strengths, 6 weaknesses, 4 opportunities, and 6 threats. Based on SWOT analysis, 8 main strategies were identified. AHP analysis shows that the top priority strategy is implementing double cash. This is crucial as sudden additional work from the Owner Surveyor (OS) often disrupts planning and resource allocation. With double cash, the project team can efficiently handle additional tasks without disturbing the existing budget, address OS decision delays, and reduce disruptions to human resources and facilities, ensuring smooth operations and timely project completion. The second priority strategy is enhancing effective communication with OS to expedite decision-making and optimize resource allocation. The third priority is managing or evaluating customer payment terms to maintain stable cash flow, reduce financial risks, and avoid project delays.